Partial Contextual Control of Semantic False Memories in the Form of Derived Relational Intrusions Following Training. - Guinther, Paul; Dougher, Michael (Psychological Record, 2014)
A modified version of the original Derived Relational Intrusions Following Training paradigm (DRIFT; Guinther & Dougher, Journal of the Experimental Analysis of Behavior, 93, 329-347; ) was used in an attempt to engineer contextually controlled semantic false memories. Participants completed a contextually controlled interrelated conditional discrimination training procedure (match to sample) without tests of symmetry or transitivity. Study list words were nominally assigned to participate in a functional equivalence class with 1 set of non-study words in 1 context but with a different set of non-study words in a different context. The study list words were then presented in 1 of the 2 contexts, between subjects, for free-recall memory testing. Subsequent transfer of the study list words' remembering function to non-study words (i.e., false recall) was found to be partially dependent upon the context in which the free recall test was administered, thus demonstrating partial contextual control of semantic false memory.